Effects of grain-based diets on the rumen and fecal bacterial communities of the North American bison (Bison bison) - Fresno Rueda, Anlly; Griffith, Jason Eric; Kruse, Carter; St-Pierre, Benoit (Frontiers in Microbiology, 2023)
To overcome the challenges of finishing bison on pasture, producers commonly feed higher energy, grain-based diets to reach market weight. However, decades of research on domesticated ruminants have shown that such diets can have profound effects on gut microbial communities. To gain further insight, the 16S rRNA gene-based study described in this report aimed to compare the composition of ruminal and fecal bacterial communities from two herds of bison heifers (n=20 / herd) raised on different ranches that were both transitioned from native pasture to a grain-based, free choice diet for approximately 100 days prior to slaughter. Comparative analyses of Operational Taxonomic Unit (OTU) composition, either by alpha diversity indices, Principal Coordinate Analysis (PCoA) or on the most abundant individual OTUs, showed the dramatic impact of diet on the composition of both rumen and fecal bacterial communities in bison. Indeed, feeding a grain-based diet resulted in a lower number of rumen and fecal bacterial OTUs, respectively, compared to grazing on pasture (p < 0.05). PCoA revealed that the composition of rumen and fecal bacterial communities from the two herds were respectively more similar to each other when they were grazing on native pastures compared to when they were fed a grain-based, free choice diet. Finally, a comparative analysis of the twenty most abundant OTUs from rumen and fecal communities, respectively, further showed that the representation of all these species-level bacterial groups was different (p < 0.05) between the two dietary treatments. Together, these results provide further insights on the rumen and fecal microbiomes of grazing bison, as well as their response to grain-based diet regimens that are commonly used in intensive ruminant production systems.